Morbidity and Mortality pattern in Neonatal ICU in a tertiary care teaching hospital of Puducherry, South India - K, Maheswari; Sharma, Neha (Pediatric Review: International Journal of Pediatric Research, 2020)
Objectives: This study was undertaken to know about the morbidity and mortality pattern of neonates admitted in neonatal ICU in a tertiary care teaching hospital. Materials and Methods: This is a hospital-based, retrospective, descriptive study, done on newborns admitted to neonatal ICU of Sri Venkateshwara Medical College Hospital and Research Centre, Puducherry from January 2018-December 2019 (24 months). Results: As about 935 neonates were admitted to neonatal ICU. About 781 neonates were analyzed. Maternal details showed that (70.6%) were educated and (29.3%) of them were uneducated. Morbidity pattern studied in 773 (98.9%) neonates showed that, neonatal jaundice (19.2%), neonatal sepsis (12.1%), TTNB (11.7%), HIE (10.9%), RDS (10.3%), was the common reason for admission. Feeding difficulties were observed in (6.5%), IDM for blood glucose monitoring (5.9%), LBW/preterm care (5.1%), meningitis (2.9%), seizures (2.7%), NEC (2.4%), MAS (2.1%), congenital anomalies (1.9%). The outcome noted in the morbidity pattern was that 99.7% were discharged and 0.25% were referred. Analysis of mortality pattern 8(1.02%) showed that, according to birth weight <1 kg (37.5%) was the most common cause of death, followed by 1-1.5 kg (25%), 1.5 -2.49 kg (25%), > 2.5 kg (12.5%). Maternal complications contributing to neonatal mortality was observed in (75%), it was not seen in (25%). The cause of death noted was prematurity with RDS and sepsis in (62.5%), septic shock with MODS in (12.5%), aspiration pneumonitis (12.5%), prematurity with HIE and pulmonary hemorrhage (12.5%). Conclusion: Neonatal jaundice, neonatal sepsis being the most common etiology for neonatal morbidity. Measures should be taken to diagnose jaundice earlier in high-risk cases. Steps should be taken to control neonatal sepsis by following sterile precautions during delivery. Prematurity and ELBW are the leading cause of neonatal mortality.